Behavioural and Physiochemical Dynamics of the Canine Estrous Cycle: A Tool for Enhancing Breeding Efficiency - Singh Gurjar, Kuldeep; Sarswat, Chandershekhar; Purohit, Shivani; Yadav, Lakshmi; Khandelwal, Priya (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Efficient canine breeding relies on accurate detection of the fertile window, particularly during proestrus and estrus. Over the last  decade, the interest in high-quality pedigree dogs as pets has surged, driven by smaller family structures and increased awareness.  As dog breeding has transformed into a blend of passion, artistry, and science, finding the optimal times for conception and breeding  requires constant effort. The present study was conducted during July to December 2024 at Jaipur (Rajasthan) to evaluate the behavioural  and physiochemical changes occurring throughout the estrous cycle in bitches to enhance their breeding efficiency. Eighteen healthy  bitches, aged 2-4 years, were assessed for behavioural changes (like aggression, tendency to run away from home, frequent urination  and flagging of tail, lordosis reflex) and physiochemical parameters (vulvar turgidity, edema, mucous membrane color, vaginal discharge,  and vaginal pH). Tail deflection and lordosis emerged as the most consistent behavioural signs of estrus. Vulvar turgidity and edema  peaked mid-cycle, while vaginal discharge and pH showed a decreasing trend toward ovulation. Though these external indicators offered  valuable guidance, individual variability limited their reliability. Therefore, combining behavioural and physiochemical assessments  provided a practical, low-cost recommendation for breeders and veterinarians to improve estrus detection and breeding efficiency,  especially where hormonal assays are not accessible. This integrated method could significantly improve timing for natural mating or  artificial insemination in domestic dogs.
Keywords: Behavioural changes; Bitches; Estrous cycle; Physiochemical changes